PENGEMBANGAN MEDIA KOMIK CERITA RAKYAT MELAYU UNTUK PENINGKATAN MINAT BACA MAHASISWA - Adisthi Martha Yohani; Nana Rahayu; Yenny Aristia Nasution (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This study addresses the lack of variety in teaching media for foreign language learning, which affects students’ motivation in reading lessons. The research aimed to design teaching materials incorporating elements of Malay culture into comics to enhance students’ reading interest. A Research and Development approach was applied using the 4-D model. The study was conducted at the Japanese Language Education Study Program, FKIP, Universitas Riau, from June to October 2022. Three validators assessed the learning media prototype through questionnaires. Data were collected via surveys and observations. Quantitative descriptive analysis was used to determine the validation scores. The results showed that the comic text display achieved an average score of 81.22% (appropriate category), image display scored 85.37%, and the role of comics as learning material scored 80.53% (good category). Student responses to the comics scored 95.36% (good category). Overall, the comics were found to have good validity as teaching materials.